(untitled) (Vietnam Journal of Agriculture and Environment, 2023)
In aquaculture, probiotics are given directly to animals to regulate their gut bacteria, enhance their immune systems, and aid digestion. Additionally, probiotics are introduced into the pond’s water to enhance the water quality and increase the chances of survival for aquatic creatures. Lactobacillus belongs to the group of lactic acid bacteria (LAB), which are considered beneficial for aquaculture. Incorporating LAB into fish feed can enhance its nutritional quality. LAB produces various digestive enzymes that aid in food breakdown and digestion, promoting growth to the host. In this study, 95 isolates of lactic acid bacteria were recovered in the gut of grass carp in Thai Binh, Bac Giang and Nam Dinh province, Vietnam. Only 9 of 95 isolates had the inhibition effects on Aeromonas hydrophila and Staphylococcus aureus. The isolates L18 showed the strongest antimicrobial activity to Aeromonas hydrophila and Staphylococcus aureus with the diameter of antimicrobial zones were 18.22 ± 0.16 mm and 10.14 ± 0.23 mm, respectively. The strain L18 was identified as Lactobacillus fermentum based on its morphological, physiological, biochemical characteristics, and 16S rRNA sequences. The L. fermentum L18 is capable of withstanding concentrations of bile salts ranging between 0.0% and 0.5%. Moreover, it can tolerate stomach acid with a pH range of 1 to 4. Furthermore, the bacterial L. fermentum strain L18 can produce extracellular enzymes that include cellulase and amylase, which are responsible for breaking down starch and cellulose substrates. Thus, the Lactobacillus L18 strain could be considered a potential antimicrobial probiotic strain against fish pathogens and should be further studied for its probiotic benefits.